2013
DOI: 10.3390/molecules181114268
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of DNA/RNA and Their Analogs via Phosphoramidite and H-Phosphonate Chemistries

Abstract: Abstract:The chemical synthesis of DNA and RNA is universally carried out using nucleoside phosphoramidites or H-phosphonates as synthons. This review focuses on the phosphorus chemistry behind these synthons and how it has been developed to generate procedures whereby yields per condensation approach 100% with very few side products. Additionally the synthesis and properties of certain DNA and RNA analogs that are modified at phosphorus will also be discussed. These analogs include boranephosphonates, metallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 48 publications
0
74
0
2
Order By: Relevance
“…An elaborate description is given under Mechanistic View, see Schemes 1 and 2. The group of Van Boeckel (Kuijpers et al [1] ) published the synthesis of well-defined, short phosphatemethylated DNA fragments according to the step-wise phosphoramidite procedure with one Fmoc-protected A nucleotide, according to Koole et al, [12][13][14] indicated as solution-phase synthesis. Meanwhile, Van Boeckel's group confirmed the backbone methylation in Koole's study.…”
Section: Controversymentioning
confidence: 99%
See 2 more Smart Citations
“…An elaborate description is given under Mechanistic View, see Schemes 1 and 2. The group of Van Boeckel (Kuijpers et al [1] ) published the synthesis of well-defined, short phosphatemethylated DNA fragments according to the step-wise phosphoramidite procedure with one Fmoc-protected A nucleotide, according to Koole et al, [12][13][14] indicated as solution-phase synthesis. Meanwhile, Van Boeckel's group confirmed the backbone methylation in Koole's study.…”
Section: Controversymentioning
confidence: 99%
“…This chemistry was described in a recent review by Roy and Caruthers. [12] Attention was also given to modified DNAs. Letsinger et al were the first chemists who synthesized natural DNA strands using phosphite triesters as intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the phosphoramidites 10a–f were isolated in excellent yields (83–98%) by following a standard phosphitylation procedure. 42 The presented strategy allows for late-stage incorporation of the respective dyes minimizing losses that typically accumulate over the course of multi-step syntheses. This is particularly crucial if the fluorophores are not readily available.…”
Section: Resultsmentioning
confidence: 99%
“…Within 7 years of this work, the first reported synthetic gene encoding the 14-amino-acid hormone, somatostatin, was expressed in recombinant Escherichia coli (Itakura et al 1977). Subsequent improvements to oligonucleotide synthesis chemistries and techniques in the early 1980s (reviewed in Caruthers 2011; Roy and Caruthers 2013) led to the development of solid-phase phosphoramidite chemistries whose robustness and fidelity allowed for automated methods to be developed to enable scalable oligonucleotide synthesis that is used to this day for the commercial synthesis of oligonucleotides. Synthetic oligonucleotides for gene synthesis applications are generally synthesized using variations of the phosphoramidite chemistry methods either on traditional column-based synthesizers or microarray-based synthesizers that will be discussed in the following sections.…”
mentioning
confidence: 99%